Legal and Ethical Aspects of Discontinuing Futile Medical Care in Poland, the United Kingdom and Italy. A Comparative-Legal Perspective - Czajkowska, Oliwia; Robak, Natalia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
Futile care encompasses a range of medical procedures that serve to sustain the vital functions of a terminally ill person, thus prolonging their dying process. This paper aims primarily to arrive at a legal and ethical characterization of the institution of futile care. In the light of pertinent laws in other countries (the United Kingdom, Italy), the authors demonstrate that it is necessary to take legislative action concerning futile care in Poland, including e.g. the institution of advanced decision and lasting power of attorney. There are certain obstacles to introducing legal norms that pertain to futile care. For one thing its normative definition is lacking while the applicable law, such as the Act on the Medical Profession, imposes an obligation on the physician to provide medical assistance in each case where delay could expose the patient to the risk of loss of life, grievous bodily injury or serious disturbance of health.